Fear Perception of the COVID-19 Pandemic in Peru - Mejia, Christian R. (2021)
Introduction: Fear is a natural response to something unknown. In the current scenario, it is important to assess it in relation to the coronavirus disease-19 (COVID-19) pandemic in Latin American countries. Objective: To determine the fear perception according to factors associated with the COVID-19 pandemic in Peru. Methods: An analytical cross-sectional study was conducted based on a virtual questionnaire. The main question was “how much fear people had of COVID-19?”, using a scale from zero (without fear) to 10 (very fear). This scale was divided into tertiles, and the upper tertile was the reference category (compared to the middle and lower tertiles). Statistical significances between fear perception of COVID-19 and sociodemographic data were calculated. Results: A total of 3887 participants responded the questionnaire about fear perception. In the multivariate analysis was found that women (adjusted prevalence ratio (aPR): 1.37; 95% confidence interval (CI) : 1.26-1.48; p<0.001), people aged 20-29 (aPR: 1.84; 95% CI: 1.06-1.50; p=0.005), 30-39 (aPR: 1.53; 95% CI : 1.28-1.82; p<0.001), 50-59 (aPR: 1.43; 95% CI: 1.12-1.84; p=0.005), and with 60 or more years (aPR: 1.46; 95% CI: 1.03-2.07; p=0.032), as well as respondents who had some risk for complications due to COVID-19 (aPR: 1.49; 95% CI: 1.32-1.69; p<0.001) were very afraid of the disease. On the other hand, people affiliated with evangelical religions (aPR: 0.79; 95% CI: 0.65-0.96; p=0.018), agnostics (aPR: 0.80; 95% CI: 0.68-0.94; p=0.008), atheists (aPR: 0.67; 95% CI: 0.48-0.95; p=0.024), and health professionals (aPR: 0.81; 95% CI: 0.70-0.93; p=0.003) were less afraid of COVID-19. Conclusion: There was a notorious fear perception of the COVID-19 pandemic by the Peruvian population. In this context, the fear was associated with important variables. Thus, the provision of further emotional support services for this population should be considered in the face of the current pandemic.